Histopathological analysis of the reproductive system of male dogs experimentally infected with Toxoplasma gondii - Arantes,Tiago Pereira (2009)
The present research aimed to describe possible histopathological alterations in the reproductive system (testicles and epididymis) of male dogs experimentally infected with Toxoplasma gondii. Canines (n=10) serologically negative for T. gondii were selected and distributed into three experimental groups: GI, 3 inoculated with 2.0 x 10(5)P strain oocysts; GII, 3 infected with 1.0 x 10(6)RH strain tachyzoites; and GIII, 4 control dogs. Antibody research (IFAT) against T. gondii was realized. Toxoplasma gondii infection was confirmed by seroconversion of the 6 males infected with tachyzoites and oocysts from postinoculation day (PID) 7 and 14, respectively. At PID 70, all dogs were submitted to orchiectomy and testicle and epididymis samples were collected and histologically processed for examination under optical microscope. The following alterations were diagnosed: mild and moderate mononuclear inflammatory infiltrate in the epididymis, moderate cellular edema, hydropic degeneration and moderate interstitial fibrosis in seminiferous tubules. The histopathological results in the present research, isolation of T. gondii in testicle and epididymis fragments by immunohistochemistry and results from the literature by other authors in different tissues, all infer that the alterations observed in dogs infected with T. gondii are suggestive of toxoplasmic infection.